"There's More Thinking to Decide": How the Childfree Decide Not to Parent. (July 2016) - Blackstone, Amy; Stewart, Mahala Dyer
The processes by which women and men decide not to have or rear children are lengthy and complex. Analysis of data from qualitative interviews with 21 women and 10 men reveals two primary themes in adults' descriptions of their decision not to have children: (1) that the decision was a decidedly conscious decision and (2) that the decision occurred as a process as opposed to a singular event. The features of these two themes are considered, as are their gendered dimensions and social and practical implications.